Accuracy of Self‐reported Diagnosis of Chronic Rhinosinusitis. (6th November 2018) - Workman, Alan D.; Parasher, Arjun K.; Blasetti, Mariel T.; Palmer, James N.; Adappa, Nithin D.; Glicksman, Jordan T.
Abstract : Large cohort studies of chronic rhinosinusitis (CRS) prevalence often include patients who have been inappropriately diagnosed with the disease. In this investigation, new patients presenting to a tertiary rhinology practice completed a screening questionnaire that included questions about self‐reported CRS status, demographic information, and symptomatology. Treating rhinologists evaluated patients according to clinical practice guideline criteria for CRS; 91 patients were ultimately diagnosed with CRS. The sensitivity of self‐report for CRS was 84%; the specificity was 82%; and the estimated negative predictive value ranged from 97% to 99%. Prior sinus surgery or oral steroid use correlated with CRS self‐report, and a concurrent self‐report of nasal polyps or nasal steroid use improved the positive predictive value of CRS self‐report. Self‐report of CRS status may represent an effective and relatively inexpensive screening mechanism for CRS in large cohort studies, particularly when combined with other associated diagnostic features that improve performance parameters of self‐report.